SUMBANGSIH ISLAM DALAM MENANGGULANGI KEHAMPAAN SPIRITUAL MASYARAKAT MODERN; TELAAH ATAS PEMIKIRAN TASAWUF SAYED HUSEIN NASR - Muh - Rusli; Rakhmawati Rakhmawati (LPPM IAIN Sultan Amai Gorontalo, 2014)
World of Sufism has sometimes been underestimated because of it away from world and even hostile.Sayed Hussein Nasr stated that Sufism is the one of alternative solution to meet the challenges of the modern era. Western and Moslems havebeen affectedby Western modernism, theyare materially established, but they sufferspiritual emptiness due to the apotheosis of material and science. Therefore, one must have the equilibrium between science and charity, and between contemplation and action. Furthermore, the problem of interfaith can be resolved through sufistic approach in which Islam is not only about religion revealed through the Qur'an to the Prophet Muhammad, but also Islam is for all of authentic religions.